RETRACTED: Recent Development of Renewable Diesel Production Using Bimetallic Catalysts - Chia, Shir Reen; Nomanbhay, Saifuddin; Ong, Mei Yin; Chew, Kit Wayne; Khoo, Kuan Shiong; Karimi-Maleh, Hassan; Show, Pau Loke (Frontiers in Energy Research, 2021)
Renewable diesel as a potential sustainable energy source in future requires catalysts to convert the feedstocks into end products. Among various type of catalysts, bimetallic catalysts are widely applied in the renewable diesel production due to their unique catalytic properties and enhanced catalytic activities, which differ from their parent monometallic catalysts. This mini review comprised of the brief introduction on technologies in producing renewable diesel and aims to discuss the underneath knowledge of synergistic interactions in bimetallic catalysts that synthesized through various techniques. The novelty of this paper is revealing the recent development of renewable diesel production, highlighting the mechanisms of bimetallic catalysts in the enhancement of the catalytic activity, and exploring their possibilities as practical solution in industrial production.